Konsep dan karakter penilaian dalam kurikulum merdeka - Faiseh, Aulitul (Maliki Interdisciplinary Journal, 2024)
English abstract. The Merdeka Curriculum, as part of education reform in Indonesia, introduces a different assessment approach compared to the previous curriculum. The assessment concept in the Merdeka Curriculum focuses on developing students’ critical thinking skills, creativity and in-depth understanding through more flexible formative and summative assessments. Assessment in this curriculum emphasizes the learning process and development of individual students, not just the final results, thus providing space for teachers to carry out authentic assessments that are relevant to students’ needs and potential. The main characteristics of assessment in the Merdeka Curriculum include flexibility, relevance and sustainability, which aims to measure student achievement in various aspects, including holistic aspects of knowledge, attitudes and skills. Additionally, this concept also involves project-based assessments, portfolios, and self-reflection to encourage meaningful learning and improve students’ skills in overcoming real-world challenges. In this way, the Merdeka Curriculum supports a more inclusive and adaptive education, which allows students to develop according to their interests and abilities.